2016
DOI: 10.5943/mycosphere/7/6/14
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal symbiosis regulates hormone and osmotic equilibrium of Lycium barbarum L. under salt stress

Abstract: Arbuscular mycorrhizal fungi (AMF) enhance salt tolerance of host plants via multiple mechanisms, but their effect on hormone mediated tolerance is unclear. The influence of AMF on hormone regulation and osmotic adjustment of Lycium barbarum L. (Goji) under salt stress was evaluated. AMF enhanced indol-3-acetic acid (IAA) in leaves and roots and abscisic acid (ABA) in leaves of Goji growing in saline soils. These changes resulted in enhanced osmotic adjustment in mycorrhizal plants, leading to higher leaf wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…In this study, the contents of salicylic acid and abscisic acid were both increased after inoculation with AMF under alkali stress. Similar results were also found in Cucumis sativus and Lycium barbarum [72,73]. The results showed that AMF significantly changed the levels of various plant hormones, which was an effective way to enhance alkali tolerance in P. tenuiflora seedlings.…”
Section: Effects Of Arbuscular Mycorrhizal Fungi On the Metabolic Prosupporting
confidence: 80%
“…In this study, the contents of salicylic acid and abscisic acid were both increased after inoculation with AMF under alkali stress. Similar results were also found in Cucumis sativus and Lycium barbarum [72,73]. The results showed that AMF significantly changed the levels of various plant hormones, which was an effective way to enhance alkali tolerance in P. tenuiflora seedlings.…”
Section: Effects Of Arbuscular Mycorrhizal Fungi On the Metabolic Prosupporting
confidence: 80%
“…AMF and plant symbiosis can promote plant growth by increasing the photosynthesis of plants under salt stress, thereby increasing the ability of plants to resist the salt stress [48,49,50,51,52,53]. In this study, a photosystem II D1 precursor processing PSB27 was found to have upregulated expression.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, AMF can increase the IAA level and promote the growth and development of host plants under stress by upregulating the expression of IAA transporter genes and downregulating the expression of auxin efflux genes [ 31 ]. In addition, AMF have a positive effect on the regulation of IAA levels in plants under drought [ 32 ], salt stress [ 33 ] and biotic stress [ 34 ]. These results suggested that the increase in IAA levels in tomato roots induced by AMF might be an important reason to promote the growth and development of tomato seedlings in continuous cropping substrates.…”
Section: Discussionmentioning
confidence: 99%